The Symbiosis of Machines and Empathy: How Human-Centric AI Leadership Drives Sustainable Organizational Excellence - Juni Suryanadi; Oktabriyantina Wulan; Hamdan Daniel (LPPM STIAB Jinarakkhita Lampung, 2026)
This study aims to analyze the effect of Human-Centric AI Leadership on Sustainable Organizational Excellence, examine the effect of Human-Centric AI Leadership on Empathy, analyze the effect of Empathy on Sustainable Organizational Excellence, and investigate the mediating role of Empathy in the relationship between Human-Centric AI Leadership and Sustainable Organizational Excellence. This study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research population consisted of employees working in organizations implementing digital transformation and AI-based systems, with a total sample of 223 respondents selected through purposive sampling techniques. Data were collected through the distribution of structured questionnaires using a five-point Likert scale and analyzed using SmartPLS 3 software. The results indicate that Human-Centric AI Leadership has a positive and significant effect on both Sustainable Organizational Excellence and Empathy. Furthermore, Empathy also has a positive and significant effect on Sustainable Organizational Excellence and significantly mediates the relationship between Human-Centric AI Leadership and Sustainable Organizational Excellence.